Differentiating between intra- and extracellular chemiluminescence in diluted whole-blood samples - Rájecký, M; Lojek, A; Cíž, M (International journal of laboratory hematology, 2012)
INTRODUCTION: The differentiation between extra- and intracellular production of reactive oxygen species (ROS) in whole blood was measured by luminol- and isoluminol-enhanced chemiluminescence (CL). METHODS: Azide (total CL inhibition), azide + horseradish peroxidase (HRP, restoring extracellular CL), superoxide dismutase + catalase (depleting extracellular ROS) and HRP (enhancing extracellular CL) were used to modulate luminol- and isoluminol-enhanced CL (10(-6) -10(-3) m luminophores) of 125× diluted whole blood which was activated by both calcium ionophore A23187 (Ca-I) and opsonized zymosan particles (OZP) separately. RESULTS: Both activators stimulated intra- and extracellular production of ROS. Luminol-enhanced CL of Ca-I-activated samples detected the intracellular ROS, and with the addition of HRP detected the extracellular CL as well. CL enhanced with isoluminol in concentrations of 10(-4) m or less was mostly extracellular. There was a mixture of intra- and extracellular CL in OZP-activated samples, probably because of the ingestion of luminophore molecules. CONCLUSION: Measurement of Ca-I-activated CL enhanced with 10(-4) m luminol is recommended for the detection of intracellular ROS. The addition of HRP leads to the detection of overall ROS production while the OZP-activated system with its addition of HRP can only be used to detect overall ROS production. Ca-I-activated CL enhanced with 10(-4) m isoluminol and with addition of HRP is recommended for the detection of extracellular CL.
Keywords: Luminescence; Blood; luminiscenční měření; Blood Cells; reaktivní formy kyslíku; Luminol; Luminescent Measurements; krev; krevní buňky; Humans; lidé; luminiscence; luminol; Reactive Oxygen Species